Assessment of Residents’ Attitudes and Satisfaction Before and After Implementation of a Smoke-Free Policy in Boston Multiunit Housing - Rokicki, Slawa (Nicotine Tob Res, 2016)
INTRODUCTION: In 2012, the Boston Housing Authority (BHA) in Massachusetts implemented a smoke-free policy prohibiting smoking within its residences. We sought to characterize BHA resident experiences before and after the smoke-free policy implementation, and compare them to that of nearby residents of the Cambridge Housing Authority, which had no such policy. METHODS: We recruited a convenience sample of nonsmoking residents from the BHA and Cambridge Housing Authority. We measured residents’ awareness and support of their local smoking policies before and 9–12 months after the BHA’s policy implementation, as well as BHA respondents’ attitudes towards the smoke-free policy. We assessed tobacco smoke exposure via saliva cotinine, airborne apartment nicotine, and self-reported number of days smelling smoke in the home. We evaluated predictors of general satisfaction at follow-up using linear regression. RESULTS: At follow-up, 91% of BHA respondents knew that smoking was not allowed in apartments and 82% were supportive of such a policy in their building. BHA residents believed enforcement of the smoke-free policy was low. Fifty-one percent of BHA respondents indicated that other residents “never” or “rarely” followed the new smoke-free rule and 41% of respondents were dissatisfied with policy enforcement. Dissatisfaction with enforcement was the strongest predictor of general housing satisfaction, while objective and self-reported measures of tobacco smoke exposure were not predictive of satisfaction. At follow-up, 24% of BHA participants had complained to someone in charge about policy violations. CONCLUSIONS: Resident support for smoke-free policies is high. However, lack of enforcement of smoke-free policies may cause frustration and resentment among residents, potentially leading to a decrease in housing satisfaction. IMPLICATIONS: Smoke-free housing laws are becoming increasingly prevalent, yet little is known about satisfaction and compliance with such policies post-implementation. We evaluated nonsmoking residents’ attitudes about smoke-free rules and their satisfaction with enforcement 1 year after the BHA implemented its comprehensive smoke-free policy. We found that while residents were supportive of the policy, they believed enforcement was low, a perception that was associated with a drop in housing satisfaction. Our findings point to a desire for smoke-free housing among public housing residents, and the importance of establishing systems and guidelines to help landlords monitor and enforce these policies effectively.